OC-028 High definition white light endoscopy (HDWLE) versus high definition with chromoendoscopy (HDCE) in the detection of dysplasia in long standing ulcerative colitis: a randomised controlled trial. (22nd June 2015) - Mohammed, N; Kant, P; Abid, F; Rotimi, O; Prasad, P; Hamlin, J; Everett, S; Rembacken, B; Hull, M; Subramanian, V
Abstract : Introduction: Patients with ulcerative colitis (UC) have an increased risk for colorectal cancer. The yield of surveillance can be improved by addition of newer endoscopic methods like chromoendoscopy (CE) 1 and HDWLE when compared to standard definition endoscopy. 2 There are no studies comparing HDCE and HDWLE. The aim of this trial is to compare the rate of detection of dysplasia in patients with long standing UC with HDWLE compared to HDCE. Method: Parallel group randomised controlled trial (clinicaltrials.gov number NCT02138318 ) in which patients with long standing UC (>10 years) requiring surveillance colonoscopy were randomised to either HDWLE or HDCE (with 0.2% indigo carmine spray). HD scopes (Olympus CF260L or 290L) and processors (Olympus Spectrum CV260 or Elite CV290) and HD monitors were used for all procedures. Time to reach caecum and withdrawal time was recorded. Presence of dysplasia was confirmed by two expert GI histopathologists. Data was analysed according to the number of patients who had dysplastic endoscopic lesions detected (per patient analysis) and also to the number of dysplastic lesions (per lesion analysis). Results: In total 53 patients were randomised to HDWLE and 50 to the HDCE arm. Baseline characteristics including duration of disease, bowel preparation, endoscopists, concomitant PSC and previous dysplasia were similar in both arms. A total of 14 dysplastic lesions (1 with high grade and 13 with low grade dysplasia) were detected in 11 patients (22%) in the HDCE arm and 6 dysplastic lesions (all low grade dysplasia) in 5 patients (9.4%) in the HDWLE arm. HDCE was significantly better (p = 0.04) than HDWLE on a per patient basis for the detection of endoscopically visible dysplastic lesions. HDCE (0.26 ± 0.6) detected more dysplastic lesions per-patient than HDWLE (0.12 ± 0.4). Withdrawal time was significantly (p < 0.001) higher in HDCE (21.2 ± 5.8 min) compared to HDWLE (13.6 ± 3.3 min). Conclusion: HDCE significantly improves the detection of dysplastic lesions in patients undergoing surveillance endoscopy for UC and should be the procedure of choice in these patients. On average it increases procedure time by 8 min over HDWLE. Disclosure of interest: None Declared. References: Subramanian V, Mannath J, Ragunath K, Hawkey CJ. Meta-analysis: the diagnostic yield of chromoendoscopy for detecting dysplasia in patients with colonic inflammatory bowel disease. Aliment Pharmacol Ther. 2011;33:304–312 Subramanian V, Ramappa V, Telakis E, et.al . High definition versus standard definition endoscopy for detection of dysplasia in colonic inflammatory bowel disease. Inflamm Bowel Dis . 2013;19:350–5